Effect of nanoparticles on color stability and mechanical and biological properties of maxillofacial silicone elastomer: A systematic review - Nithin Kumar Sonnahalli; Ramesh Chowdhary (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim of this systematic review was to evaluate the effect of addition of various nanoparticles into maxillofacial silicone elastomer on color stability and mechanical and biological properties of the silicone elastomer. Settings and Design: This systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines(PRISMA). Materials and Methods: The electronic database search in MEDLINE/PubMed was based on population (silicone elastomer), intervention (nanoparticles), comparison (unreinforced silicone elastomer with nanoparticle-reinforced silicone elastomer), outcome (color stability and mechanical, physical, and biological properties), i.e., PICO framework. The key words used are ("maxillofacial silicone" OR "silicone elastomer" OR "facial silicone") AND ("nanoparticles" OR "Nano-oxides") AND ("colour stability" OR "Hardness," "tensile strength" OR "tear strength" OR "antifungal activity"). Results: The database search resulted in 2099 studies, of which 2066 articles were excluded as they were irrelevant, duplicates, and data were not available. The remaining 33 full-text articles were assessed for eligibility, out of which 2 articles were in Chinese language, 3 articles were thesis documents, and 8 were review articles. A total of 12 articles were excluded and the remaining 20 articles were included. One article was yielded by hand search of references of included studies. A total of 21 studies were included in the present systematic review. Conclusion: With the available evidence in the literature, it can be concluded that addition of nanoparticles at various concentrations may improve the physical and mechanical properties and color stability of the prosthesis made from the silicone elastomers.